2018
DOI: 10.1002/nau.23568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of severity of urinary incontinence on quality of life in women

Abstract: This study demonstrated that even mild urinary leakage significantly reduces the QoL, while subsequent increase in the degree of incontinence has only minimal additional effect. There was no linear correlation between incontinence severity and QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 17 publications
2
50
1
3
Order By: Relevance
“…Similar to previous studies (9,(27)(28)(29), we evaluated the severity of UI using the validated ISI. Other studies have used various measurement methods for the evaluation of UI severity, including the 24hour pad test (30), self-perceived incontinence severity (mild, moderate, or severe; 12), and an invalidated questionnaire (6). It was reported that the 24-hour pad test does not have a standardized protocol and that urine leakage can differ based on the patient's physical activity level (30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to previous studies (9,(27)(28)(29), we evaluated the severity of UI using the validated ISI. Other studies have used various measurement methods for the evaluation of UI severity, including the 24hour pad test (30), self-perceived incontinence severity (mild, moderate, or severe; 12), and an invalidated questionnaire (6). It was reported that the 24-hour pad test does not have a standardized protocol and that urine leakage can differ based on the patient's physical activity level (30).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used various measurement methods for the evaluation of UI severity, including the 24hour pad test (30), self-perceived incontinence severity (mild, moderate, or severe; 12), and an invalidated questionnaire (6). It was reported that the 24-hour pad test does not have a standardized protocol and that urine leakage can differ based on the patient's physical activity level (30). In clinical settings, subjective measurements for the determination of the severity of UI are preferred due to their cost-effectiveness, time-efficacy, and good correlation with objective measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the worldwide rise of the proportion of older people (aged 65 years and over), a rise of pelvic floor disorders is seen [3,4]. PFDs considerably reduce the well-being and the quality of life by interfering with daily and social activities, which in the worst case leads to isolation [5,6].…”
Section: Introductionmentioning
confidence: 99%